PP.40.22: ASSOCIATION OF MATRIX METALLOPROTEINASE 2 WITH TARGET ORGAN DAMAGE IN RESISTANT HYPERTENSION. (June 2015) - Sabbatini, A.; Barbaro, N.R.; Faria, A.P. Cabral De; Ritter, A.; Modolo, R.; Pinho, C.; Moreno, B.; Fontana, V.; Moreno, H.
Abstract : Objective: This study evaluates the association between matrix metalloproteinase 2 (MMP-2) and its tissue inhibitor, TIMP-2, with the phenotypic characteristics of resistant hypertension subjects. Design and method: A total of 58 RH patients and 101 mild to moderate hypertensive (HT) patients were included. Left ventricular hypertrophy (LVH), BMI and body composition (lean mass and fat mass), renal damage (microalbuminuria), BP, and plasma levels of MMP-2, TIMP-2, and aldosterone were analyzed. Statistical analysis: The groups were compared by the Student's t test or Mann-Whitney according to data distribution. A significance level of alpha = 0.05 was adopted. Results: RH patients had higher LVMI [112.2 g/m 2 (88.5 - 135) vs. 100.1 g/m 2 (86.8 - 119.4); p = 0.03], microalbuminuria [16.8 mg/g (9 – 66.4) vs. 5.9 mg/g (4.1 – 12.9); p < 0.001], aldosterone [92.8 pg / ml (48 – 176.2) vs. 59.9 pg/ml (37.7 – 91.4); p = 0.002], BP [149 mmHg (134 – 155.5) vs. 140 mmHg (133 -151.2); p = 0.046], BMI [31.2 kg/m 2 (27 – 35.4) vs. 27.6 kg/m 2 (24.8 – 32.1); p = 0.001], FM (fat mass) [25.9 kg (18.7 – 34.1) vs. 19.9 kg (14.7 – 27.6); p = 0.002], and TIMP-2 levels [91.3 ng/ml (80.2 – 106.3)vs. 567.8 ng/ml (54.7 – 87.3); p < 0.001] compared to HT. On the other hand, patients with HT had increased MMP2 / TIMP2 ratio [130.9 (82.5 – 211.9) vs. 82.7 (65.3 – 138.8); p = 0.001] compared to RH patients. Conclusions: As expected, RH had a worse CV condition related to HT patients. Nonetheless, this group showed significantly higher levels of TIMP-2, suggesting the presence of a protective factor in front of the unfavorable clinical and metabolic profile of these patients.